Mixed convection of EG/NEPCM inside a lid-driven cavity with a rotating cylinder - Zhang, Yang; Lin, Haitao; Chaturvedi, Rishabh; Singh, Pradeep Kumar; Mansir, Ibrahim B.; Zhang, KePing; Alhoee, Javid (Case studies in thermal engineering, 2023)
Using the potential of nature's phenomena such as free convection phenomenon could help to cooling a piece, such as a moving hot plate in lid-driven problems. Moreover, adding modern nanostructures named nano-encapsulated phase change material (NEPCM) with ability of phase transition could greatly improve the heat transfer processes. In this study, the mixed convection of ethylene glycol (EG) and NEPCM was simulated inside a lid-driven cavity with a rotating cylinder to evaluate the contribution of Grashof number, cylinder speed, and concentration of NEPCM on the heat transfer characteristics. Hence, the findings of current numerical study indicated that the NEPCM with 6% concentration increased the mean Nusselt number by 41.7%. Moreover, the cylinder speed enhanced the mean Nusselt number by 38.7%. Finally, there was an optimum value for concentration occurred in 4% brought for Grashof number of 104.